Welcome to India - Costain, Meredith; Collins, Paul, 1954-; Duck, Vaughan; Pascoe, Stephen (Philadelphia : Chelsea House Publishers, 2002)
Presents an inside view of life in India, discussing the country's schools, families, sports, leisure, culture, festivals, religion, food, shopping, landscape, climate, plants and animals, cities, landmarks, industry and agriculture, transportation, and history and government. Includes a fact file, recipe, activity, and glossary.
Includes index.
4.7
3-6
Keywords: India -- Juvenile literature; India; India